Embodied Intelligence in Plants. Issue 1 (1st October 2022) - Mazzolai, Barbara; Dottore, Emanuela Del; Tramacere, Francesca; Mondini, Alessio; Margheri, Laura
Abstract: Envisioning a rethink of the design of robotic systems is necessary for a step-change in developing more sustainable and efficient artificial machines. Recent trends in robotics have embraced the idea of taking inspiration from plants to create energy-efficient components, self-morphing growing robots, biodegradable robots, and the definition of novel models of embodied intelligence and morphological computation. Plants can move and grow in air, soil, and water. They can sense and explore the surrounding environment, continuously grow and adapt their shape, and even communicate with each other and with other organisms. Their role for us and our planet is fundamental: for the oxygen we breathe, the food we eat, and to preserve the equilibrium of biodiversity and global climate. Understanding their functioning is of paramount importance and represents an opportunity not only for scientific advancements but also for rethinking the design of artificial technologies that can better integrate with our ecosystems. With a specific focus on the aspects of plants' embodied intelligence, this contribution highlights some of the features of plants that have been investigated for engineering design and introduces new research lines currently at the forefront of the field. A perspective for innovation in science and robotics inspired by plants is also discussed, with a vision toward a new generation of sustainable robots.